2008
DOI: 10.1128/mcb.01287-07
|View full text |Cite|
|
Sign up to set email alerts
|

Transforming Growth Factor α (TGFα)-Stimulated Secretion of HSP90α: Using the Receptor LRP-1/CD91 To Promote Human Skin Cell Migration against a TGFβ-Rich Environment during Wound Healing

Abstract: Jump-starting and subsequently maintaining epidermal and dermal cell migration are essential processes for skin wound healing. These events are often disrupted in nonhealing wounds, causing patient morbidity and even fatality. Currently available treatments are unsatisfactory. To identify novel wound-healing targets, we investigated secreted molecules from transforming growth factor ␣ (TGF␣)-stimulated human keratinoytes, which contained strong motogenic, but not mitogenic, activity. Protein purification allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
231
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(242 citation statements)
references
References 51 publications
(71 reference statements)
7
231
0
4
Order By: Relevance
“…One of the most intriguing findings and the basis of this study is the unprecedented specificity with which TGF-␣, but not EGF, triggers Hsp90␣ secretion only in primary human keratinocytes (the crucial epidermal cell type for skin wound closure). Neither TGF-␣ nor EGF triggers exosome or Hsp90 secretion in human dermal fibroblasts or human microvascular endothelial cells from the dermis (33). However, human dermal fibroblasts and human microvascular endothelial cells secrete Hsp90␣ under other microenvironmental stress signals, such as hypoxia (37,38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most intriguing findings and the basis of this study is the unprecedented specificity with which TGF-␣, but not EGF, triggers Hsp90␣ secretion only in primary human keratinocytes (the crucial epidermal cell type for skin wound closure). Neither TGF-␣ nor EGF triggers exosome or Hsp90 secretion in human dermal fibroblasts or human microvascular endothelial cells from the dermis (33). However, human dermal fibroblasts and human microvascular endothelial cells secrete Hsp90␣ under other microenvironmental stress signals, such as hypoxia (37,38).…”
Section: Discussionmentioning
confidence: 99%
“…The protocols for using lentiviral systems for gene downregulation and gene upregulation, including virus packaging, isolation, infection, and analyses, were as previously described (33,37,42). The pRRLsinh-CMV system was used to overexpress exogenous genes such as the wt and mutant PRAS40 cDNAs.…”
Section: Methodsmentioning
confidence: 99%
“…The widely accepted specific isoform which can be secreted is heat shock protein 90alpha (Hsp90α) [17][18][19][20][21][22][23][24][25][26][27][28][29], whereas some researchers have also identified that heat shock protein 90beta (Hsp90β) localize outside of certain cell types [20,30,31]. Work by Jay and colleagues has provided the most compelling evidence that Hsp90α, not Hsp90β, can be detected extracellularly with functional proteomic and specific antiHsp90α antibody [24].…”
Section: Commentarymentioning
confidence: 99%
“…PLCγ1-PKCγ signaling axis mediates Hsp90α plasma membrane translocation [28]. Hsp90α has no to-be-secreted signal peptide, and the presently well accepted secretory pathway is through exosome [21,33,34]. Our group reported that overexpression of PKCγ [28] or Rab3D [35] can regulate the secretion of Hsp90α through the increase of exosome release.…”
Section: Commentarymentioning
confidence: 99%
“…The expression of CD91 receptor in human and mouse monocytes and dendritic cells and its key role in the phagocytosis of apoptotic cells and crosspresentation of antigenic peptides is well-established [6][7][8][9][10][11][12], whereas CD91 receptor has been shown to participate in the phagocytic capacity of mouse neoplastic mammary epithelial cells [14]. Furthermore, CD91 receptor has been implicated in the migration/ invasion of human keratinocytes and retinal pigment cells [15,16].…”
Section: Introductionmentioning
confidence: 99%